Enhanced microwave absorption by arrayed carbon fibers and gradient dispersion of Fe nanoparticles in epoxy resin composites. (January 2016) - Shah, Asif; Ding, Ang; Wang, Yonghui; Zhang, Li; Wang, Dongxing; Muhammad, Javid; Huang, Hao; Duan, Yuping; Dong, Xinglong; Zhang, Zhidong
Abstract: Influences of the arrayed carbon fibers (CFs) and gradiently dispersed Fe nanoparticles (NPs) inside epoxy resin (ER) matrix on the microwave absorption and mechanical properties were investigated. As a microwave absorbent, the Fe NPs were synthesized by an arc discharge plasma method and subsequently surface-modified by using of silane coupling agent (KH-550) to improve their dispersion in organic ER matrix. To measure the naturalistic electromagnetic and mechanical properties of such nanocomposite plates, a series of square plates (20 × 20 cm 2 ) were fabricated by filling the modified Fe NPs (30 wt.%) with/without orientated CFs at different mass percentages (0, 1.38 wt.%, 2.76 wt.% and 5.52 wt.%) into the ER matrix. The excellent microwave absorption of nanocomposite plate occurred as the direction of CFs was vertical to that of incident microwave, in such case the multi-reflections of microwave were caused by CFs and favors to create a great absorption probability to Fe NPs. A well matched input impedance of the plate to air is necessary for the effective entrance of incident microwave and to be attenuated by the structural resonance and electromagnetic losses. The input impedance of nanocomposite plate is mainly determined by the content of absorbent (Fe NPs with a gradient dispersion), CFs (with orientations to incident microwave, i . e . vertical, parallel or perpendicularly cross-linked to each other) and the geometric configuration (sizes of the plate, distribution of each components, etc.). It was figured out that the nanocomposite plate (30 wt.% of Fe NPs, 5.52 wt.% of CFs vertical to incident microwave) exhibits a higher reflection loss (RL) of −26.8 dB at 4.9 GHz, in which the structural resonances, appropriate conductivity, dielectric polarization and impedance matching were involved. The effects of gradiently dispersed Fe NPs and the arrayed CFs with orientations on the electromagnetic and mechanical properties were emphasized and investigated.